ASSESSING TEACHING AND LEARNING PROCESSES THROUGH REFLECTIVE LEARNING JOURNAL: A Classroom Action Research on the 11th Graders of SMA Dharma Karya UT, South Tangerang, Indonesia - *, Zaitun; Nurfisi Arriyani,; Budianto, Dede (IJRDO- Journal of Educational Research, 2020)
In TEFL, the processes of both teaching and learning play prominent roles toward the successfulness of the students’ achievements. Thus, these processess should be assessed and the assessment coming from the students’ sides will help the teachers to see the real problems faced by their students. The purpose of this classroom action research is to describe students’ reflections on the processess of teaching and learning through reflective learning journal. Total number of 19 students of 11th grade of Senior High School Dharma Karya UT, Tangerang Selatan, Indonesia, participated in this study. The research was conducted in 2 cycles and each cycle consisted of 2 meetings and each meeting covered 2 learning hours (2 x 45 minutes). Reflective learning journal writing was used as the instrument in collecting the data. It was distributed to the students before the treatment and after. The results of the study were analysed by using RMIT reflective cycle (2006) in which the writers only focused on the ‘reflection’ domain. The findings revealed that before the treatments, the students put negative reflections on English teaching and learning process. While after the treatments, their reflections were strongly positives.